Examining Accountability Mechanisms in Nepalese Savings and Credit Cooperatives: An Evidence from the Deposit Repayment Crisis - Lohani, Sagar (Journal of Advanced Academic Research, 2025)
Savings and Credit Cooperatives (SCCs) are an important medium for promoting financial inclusion in rural areas of Nepal, where reaching formal financial services is nearly impossible for the poor. Nevertheless, recent collapses of deposit repayment in several SCCs have indicated a considerably weak governance that puts member confidence and longer-term sustainability of these institutions at risk. Only in 2023/24 financial year, the cooperative fraud cases caused loss of Rs. 11.68 billion. Hundreds of suspects participate, but few are apprehended. From 2014, over 22,000 complaints with claims of NPR 10 billion have been registered revealing deep systemic weaknesses within the sector. Using case study data triangulated from national-level government reports, investigative media articles and academic research, this research is undertaken within a qualitative framework to analyses the failures of governance systems and accountability structures which culminated in the crisis. The analysis finds multiple key weaknesses, such as inadequate internal control systems and lack of accountability and transparency in operations; minimal member participation for governance; and the widespread fragmented regulatory oversight. It is therefore suggested that the current accountability measures may be ineffective, putting members' funds at risk, which in turn could lead to financial mismanagement and loss of trust amongst cooperative members. The report calls for immediate reform, including improved democratic member participation; better financial reporting with greater transparency and quality; stronger external audit functions; expedited judicial processes to bring fraudsters to book and recapture stolen assets. More coordination among the regulator, cooperatives bodies and law enforcement agencies are needed to regain trust in order for SCCs to carry on with helping Nepal achieve its goal of inclusive economic growth and sustainable development.